Enabling genome editing in tropical maize lines through an improved, morphogenic regulator-assisted transformation protocol - Hernandes-Lopes, José; Pinto, Maísa Siqueira; Vieira, Letícia Rios; Monteiro, Patrícia Brant; Gerasimova, Sophia V.; Nonato, Juliana Vieira Almeida; Bruno, Maria Helena Faustinoni; Vikhorev, Alexander; Rausch-Fernandes, Fernanda; Gerhardt, Isabel R.; Pauwels, Laurens; Arruda, Paulo; et al. (Frontiers in Genome Editing, 2023)
Genome editing (GE) is a powerful tool to accelerate plant breeding, but its large-scale application still confronts significant challenges. Prominently among these is the recalcitrance to traditional genetic transformation protocols exhibited by many genotypes of important crop species. Despite the widespread use of a few maize genotypes amenable to genetic transformation, these are unsuitable for agronomic tests in field trials or commercial applications. This hindrance is somewhat aggravated by the fact that most of the known transformable maize lines are adapted to temperate geographies, whereas a considerable proportion of maize production happens in the tropics. To overcome the low efficiency and genotype dependency of genetic transformation, various techniques have recently been developed and are constantly being refined. Ectopic expression of morphogenic regulators (MRs) is among the most promising approaches to achieve "universal" transformation and GE capabilities in maize. Here, we report the successful GE of agronomically relevant tropical maize lines using a MRs-based protocol previously optimized for the B104 temperate inbred line. To this end, we used a CRISPR/Cas9-based construct aiming at the knockout of the VIRESCENT YELLOW-LIKE (VYL) gene, which results in an easily recognizable phenotype.Three out of five tropical lines were amenable to transformation, with efficiencies reaching up to 6.63%. Remarkably, 97% of the recovered events presented indels at the target site, which were inherited by the next generation. These results demonstrate efficient GE of important tropical maize lines, expanding the current availability of GE-amenable genotypes of this important crop.